Annexin A protein family: Focusing on the occurrence, progression and treatment of cancer - Zhang, Huhu; Zhang, Zhe; Guo, Tingting; Chen, Guang; Liu, Guoxiang; Song, Qinghang; Li, Guichun; Xu, Fenghua; Dong, Xiaolei; Yang, Fanghao; Cao, Can; Zhong, Di; et al. (Frontiers in Cell and Developmental Biology, 2023)
The Annexin A protein family is a well-known tissue-specific multigene family encoding Ca2+ phospholipid-binding proteins. There is a considerable amount of literature on high levels of ANXA proteins are expressed in various malignant diseases such as cancer, atherosclerosis and diabetes. In this review, we focus on the structural and biological properties of the ANXA protein family, including the multifaceted mechanisms of the ANXA protein family in regulating biological processes in cancer progression and therapeutic response. In addition, we describe the role of the ANXA protein family in the diagnosis of different types of cancer, drug resistance and the progress related to the development of ANXA inhibitors. These data suggest that ANXA proteins are new class of targets whose regulation offers new opportunities for cancer diagnosis and treatment.